Investigation of genes associated with primary open-angle glaucoma (POAG) using expression profile analysis - Hosseini, Sahar Sadat; Abedi, Zahra; Maghsoudloo, Mazaher; Sheikh Beig Goharrizi, Mohammad Ali; Shojaei, Ahmad (Journal of Ophthalmic and Optometric Sciences, 2019)
Glaucoma is recognized as one of the most common causes of global blindness observed in various types such as primary open-angle glaucoma (POAG). This condition is characterized by progressive optic neuropathy, leading to damage of optic nerve ﬁbers. Having no symptoms at the beginning, glaucoma results in decreased vision and eventually blindness over several years. Early treatment can prevent the progression of the disease. We performed a study to evaluate differential gene expression in normal control and POAG cases. A total of 179 DEGs were discovered with 60 up-regulated and 119 down-regulated genes. After the selection of DEGs, we constructed the protein-protein interaction network. The result of GO enrichment showed the DEGs involved in antioxidant activity, haptoglobin binding, and oxygen carrier activity. Then Four modules of the primary protein network were obtained using a STRING database, using the K-means method. Next, gene ontology analysis and Kyoto encyclopedia of genes and genomes pathway enrichment were performed for four modules. These genes include TYRP1, FMOD, OGN, PAX6, COL8A2, HLA-DPA1, and HLA-DMB. The results showed that the Selected module is highly related to glaucoma pathogenesis genes. Using integrated bioinformatical analysis, we have identified DEGs candidate genes and pathways involved in glaucoma, which could improve our understanding of the cause and underlying molecular events, and these candidate genes and pathways could be therapeutic targets for glaucoma.